Scholar-Teachers of Middle School Physics and the Mechanism of Their Teaching-Research Transformation - Gao, Xudong; He, Zelong (Research and Advances in Education, 2026)
Through a series of questionnaires, this research mainly analyzed the differences in knowledge levels and the issue of teaching-research transformation among middle school physics teachers with different educational background. It is found that the relatively insufficient reserve of interdisciplinary knowledge is common across all academic qualification stages, and this phenomenon is particularly prominent among junior high school physics teachers. Master’s degree physics teachers have the lowest teaching-research transformation ability, which is related to their strong academic utilitarianism. Moreover, master’s degree physics teachers show the most significant academic utilitarianism, on the base of influenced by the professional title environment, this characteristic is more prominent among female teachers group. Based on the above findings, this research constructs a “Teaching-scholar model” for middle school physics teachers and puts forward relevant practical suggestions. It is expected to provide theoretical and practical references for enhancing the matching degree between the professional abilities of middle school physics teachers and their academic qualification levels.